“À vista da planta fresca”: ciência, imagem e natureza nos estudos de Francisco Freire Alemão - Silva, José Felipe Oliveira da (2024)
The botanist and physician Francisco Freire Alemão (1797-1874) was a prominent figure in nineteenth-century national science; known for his work in the Scientific Exploration Commission (1859-1861), as well as for a vast production of botanical illustration. Allemão's drawings were true detailed treatises of the parts of a plant (morphology): its organs, reproductive parts, leaf structure; unlike many drawings and paintings of the time - which depicted entire plants or composed a landscape - his drawings had a scientific function: botanical description. This description met criteria that passed through the realism and verifiability of the notes and illustrations in relation to the described object. The role of sight in the construction of scientific knowledge was prominent, as natural history was configured as the naming of the visible. However, it is not a matter of simple copying, but of establishing structures of visibility - the botanical structure. Faced with this question, we are not interested in perceiving the 'quality' of Allemão's drawings and notes in reproducing plants, but how he instrumentalized the drawings as resources of scientificity in his studies. How he, situated historically in nineteenth-century visual culture, produced ways of 'making visible' the plants and landscapes he described, that is, how the construction of a gaze occurred. From this perspective, we will analyze the iconography (drawing of plants) in his botanical studies, such as his handwritten notes made on his excursions through the forests of Medanha (RJ), his Travel Diary of the Scientific Commission to Ceará, his correspondence with other naturalists in Brazil and Europe, as well as other productions of botanical iconography from the nineteenth century.